Effects of E407a on the viability, metabolic and functional activity of dermal fibroblasts - Anton Tkachenko; Volodymyr Prokopiuk; Anatolii Onishchenko; Maria Shevchenko (National Scientific Medical Center, 2021)
Aim. To evaluate the effects of semi-refined carrageenan (E407a) on the viability, metabolic and functional activity of skin fibroblasts in vitro. Materials and methods. Various concentrations of E407a (0 - 10 mg/ml) were incubated for 24 h with skin fibroblast cultures isolated from rat embryos. The viability of cells exposed to semi-refined carrageenan was assessed by the neutral red uptake assay. MTT test was selected to estimate the metabolic activity of cells. In addition, scratch assay was used to determine the functional activity of dermal fibroblasts.    Results. Direct exposure to semi-refined carrageenan did not affect the viability of rat dermal fibroblasts, evidenced by the results of MTT and neutral red uptake assays. However, experimental data of MTT and scratch assays revealed that high concentrations of this food additive increased the metabolic activity of fibroblasts and diminished the motility of these cells, suggesting that E407a is cytotoxic at high concentrations.  Conclusion. Food-grade semi-refined carrageenan is cytotoxic towards skin fibroblasts at high concentrations.